Test of the Effectiveness of Moringa Oleifera Leaf Extract Cream on the Healing Process of Cut Wounds on the Skin Surface of Male Wistar Rats (Rattus Norvegicus) - Triastuti, Yulia; Nadya Nazimuddin Putri; Muhammad Nawal Hasya (Jurnal EduHealth, 2023)
Everyone there must have been injured in some way. Moringa Oleifera leaves have significant antioxidant activity and are just one of many plant-based treatments used to treat pain and speed wound healing. This study aims to ascertain if a cream made from the extract of moringa leaves (Moringa oleifera) accelerates the recovery of damages caused by cuts. This study strategy employs an actual or laboratory experimental design based on a pre-post test with a control group. Twenty adult male Wistar rats (Rattus norvegicus) were used. Mice were acclimatized, phytochemicals were screened, and treatment and monitoring were performed using dermapen wounds during the investigation. The Kolmogorov-Smirnov test, One-Way Analysis of Variance (ANOVA), and LSD post hoc Test were used to examine the research data in SPSS. Results from a 14-day study on the effects of a cream containing Moringa leaf extract on the wound healing of male Wistar rats (Rattus norvegicus) led researchers to this conclusion. In a recent phytochemical study, flavonoids, saponins, tannins, and alkaloids, known to have therapeutic benefits due to their high antioxidant content, were found in Moringa leaf extract. The secondary metabolite chemicals found in Moringa leaf extract significantly affected wound healing, with the best effects shown at an extract level of 10%.